2021
DOI: 10.4269/ajtmh.20-1305
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic Recommendations for the Management of Anticoagulation and Venous Thrombotic Disease for Hospitalized Patients with COVID-19 in Low- and Middle-Income Countries

Abstract: New studies of COVID–19 are constantly updating best practices in clinical care. Often, it is impractical to apply recommendations based on high-income country investigations to resource limited settings in low- and middle-income countries (LMICs). We present a set of pragmatic recommendations for the management of anticoagulation and thrombotic disease for hospitalized patients with COVID-19 in LMICs. In the absence of contraindications, we recommend prophylactic anticoagulation with either low molecular weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…The study compared 28-day mortality in severe COVID-19 patients who received prophylactic anticoagulation against those who did not receive any anticoagulant, and they found that the 28-day mortality was signi cantly lower in heparin-users as compared to non-users, particularly in patients with markedly elevated D-dimer and those with a higher sepsis-induced coagulopathy (SIC) score (10). This nding was further supported by other studies (11,12), and as a result standard dose thromboprophylaxis was adopted as part of routine clinical care for COVID-19 patients who require inpatient care (7,13). Despite the use of low-dose anticoagulation however, in some studies ( 14), a high proportion of patients were still developing life-threatening thrombotic complications.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…The study compared 28-day mortality in severe COVID-19 patients who received prophylactic anticoagulation against those who did not receive any anticoagulant, and they found that the 28-day mortality was signi cantly lower in heparin-users as compared to non-users, particularly in patients with markedly elevated D-dimer and those with a higher sepsis-induced coagulopathy (SIC) score (10). This nding was further supported by other studies (11,12), and as a result standard dose thromboprophylaxis was adopted as part of routine clinical care for COVID-19 patients who require inpatient care (7,13). Despite the use of low-dose anticoagulation however, in some studies ( 14), a high proportion of patients were still developing life-threatening thrombotic complications.…”
mentioning
confidence: 63%
“…All this evidence and recommendations however are from studies done in high-income nations and require patient strati cation based on laboratory tests like D-dimer, which are typically unavailable in most low-and middleincome settings. A pragmatic recommendation for hospitalized COVID-19 patients in low-and middle-income countries (LMICs) indicated administration of prophylactic anticoagulation with either Low Molecular Weight Heparin (LMWH) or unfractionated heparin (UFH) for all hospitalized COVID-19 patients in LMICs if there are no contraindications (7). Furthermore, the review recommended against the initiation of empiric therapeutic anticoagulation without clinical suspicion for venous thromboembolism (VTE).…”
Section: Introductionmentioning
confidence: 99%
“…The study compared 28-day mortality in severe COVID-19 patients who received prophylactic anticoagulation against those who did not receive any anticoagulant, and they found that the 28-day mortality was signi cantly lower in heparin-users as compared to non-users, particularly in patients with markedly elevated D-dimer and those with a higher sepsis-induced coagulopathy (SIC) score (10). This nding was further supported by other studies (11,12), and as a result standard dose thromboprophylaxis was adopted as part of routine clinical care for COVID-19 patients who require inpatient care (7,13). Despite the use of low-dose anticoagulation however, in some studies (14), a high proportion of patients were still developing life-threatening thrombotic complications.…”
Section: Introductionmentioning
confidence: 84%
“…All this evidence and recommendations however are from studies done in high-income nations and require patient strati cation based on laboratory tests like D-dimer, which are typically unavailable in most low-and middle-income settings. A pragmatic recommendation for hospitalized COVID-19 patients in low-and middleincome countries (LMICs) indicated administration of prophylactic anticoagulation with either Low Molecular Weight Heparin (LMWH) or unfractionated heparin (UFH) for all hospitalized COVID-19 patients in LMICs if there are no contraindications (7). Furthermore, the review recommended against the initiation of empiric therapeutic anticoagulation without clinical suspicion for venous thromboembolism (VTE).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation